IMPLEMENTASI METODE PHONIC DALAM PEMBELAJARAN MEMBACA PERMULAAN DI KELAS 1 MADRASAH IBTIDAIYAH AROHMAH DADAHA - Nur Islamy, Astri; Rahma Ramadani (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to describe the implementation of the phonic method in beginning reading instruction for first-grade students at Madrasah Ibtidaiyah Arohmah Dadaha and to examine the students’ learning outcomes following its application. The background of this research stems from the issue of low initial reading ability among students, as many are still unable to read simple words due to weak mastery of phonemes and graphemes. This research employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The research subjects consisted of the first-grade teacher and students at MI Arohmah Dadaha. The results show that the implementation of the phonic method involves introducing letter sounds individually, practicing the combination of sounds into syllables and words, and utilizing visual aids such as letter cards and pictures. Students demonstrated high enthusiasm, active participation in learning activities, and gradual improvement in their initial reading skills. Therefore, the phonic method is proven effective in helping students recognize letter sounds, form syllables, and read simple words phonetically. This research provides valuable insights for the development of beginning reading instruction, especially at the elementary madrasah level.